Identifikasi Ektoparasit Ikan Nila (Oreochromis niloticus) - Suardi, Magfira; Dhafir, Fatmah; Sabran, Moh.; Sutrisnawati, Sutrisnawati; Ramadhan, Achmad; Agni, Raya (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims is to identify the types of ectoparasites affecting Nile tilapia (Oreochromis niloticus). This research employed a survey method with purposive sampling technique. Fish samples were collected from two different locations, namely a tarpaulin pond and a soil pond in Binangga Village, Marawola District, Sigi Regency. Ten fish were sampled from each location and subsequently identified in the Biology Education Laboratory at Tadulako University. Observations were made on the external parts of the Nile tilapia, including the mucus, gills, fins, and tail. The parameter observed was the type of ectoparasite infecting the Nile tilapia. The results indicated the identification of five ectoparasite species: Dactylogyrus sp., Gyrodactylus sp., Attheyella sp., Cichlidogyrus sp., and Unitubulotestis sardae in 20 Nile tilapia samples. The highest prevalence of ectoparasites was found in the tarpaulin pond. However, both the tarpaulin and soil ponds shared one common ectoparasite species, Unitubulotestis sardae. The conclusion of this study is that Nile tilapia in both locations are infected by various ectoparasite species, with differences in prevalence between the tarpaulin and soil ponds.